The Importance of Place in Corporate Identity. An Investigation on the Presence of Old Dutch Firms on the Internet - Brouwer, Aleid E.; Pellenbarg, Pieter (European Spatial Research and Policy, 2011)
This paper investigates how old Dutch firms display their corporate identity on the Internet, with special attention paid to location and place. Several scholars argue that the Internet would create the ‘end-of-geography’. Current empirical investigation found that incumbent firms display a strong sense-of-place in the presentation of ‘self’ on their websites. Location is important for old firms’ images, underlining the importance of embeddedness. Location remains important when firms compete on the ‘global level’ on the Internet. This paper therefore contributes to the understanding of place and local embeddedness of firms in the ‘global internet space’.